Scalable Bio Marker Combinations for Early Stroke Diagnosis: A Systematic Review - Baez, Saiyet de la C.; García del Barco, Diana; Hardy-Sosa, Anette; Guillen Nieto, Gerardo; Bringas-Vega, Maria Luisa; Llibre-Guerra, Jorge J.; Valdes-Sosa, Pedro (Frontiers in Neurology, 2021)
Background: Acute stroke treatment is a time-critical process where every minute counts. Laboratory biomarkers are needed to aid clinical decisions imaging in diagnosis. Though imaging is critical for this process, these biomarkers may provide additional information to distinguish actual stroke from its mimics, monitor patient evolution, and the effect of potential neuroprotective strategies. For such biomarkers to be effectively scalable to public health in any economic setting, these must be cost/effective and noninvasive. We hypothesized that blood-based combinations (panels) of proteins might be the key to this approach and explored this possibility through a systematic review. Methods: We followed PRISMA guidelines for systematic reviews. Initially, the broader search for biomarkers for early stroke diagnosis yielded 704 hits, with five added manually. We then narrowed the search to combinations (panels) of protein markers obtainable from the blood. Results: A total of 12 articles dealing with blood-based panels of protein biomarkers were included in the systematic review. We observed that NR2 peptide (Ab against NR2 fragment) and GFAP are brain-specific markers related to the stroke process. vWF, MMP-9, and S100β have been widely used as biomarkers, while others as IMA index, AT-III, and Fibrinogen have not been evaluated in combination. We proposed a new combination of biomarkers for future validation: Panel 1 (NR2 + GFAP + MMP-9 + vWF + S100β), Panel 2 (NR2 + GFAP + MMP-9 + vWF + IMA index) and Panel 3 (NR2 + GFAP + AT-III + fibrinogen). Conclusions: More research is needed to validate, identify, and introduce into medical practice useful biomarkers for Stroke recurrent or diagnosis in a scalable way. The evidence indicates that the most promising approach is to combine a panel of different blood-based proteins to provide acceptable diagnostic precision for health interventions. After a systematic review, we suggest three novel biomarker panels based on results in the literature and an interpretation based on Stroke pathophysiology